Visual field asymmetries in visual evoked responses - Hagler, Donald J. (J Vis, 2014)
Behavioral responses to visual stimuli exhibit visual field asymmetries, but cortical folding and the close proximity of visual cortical areas make electrophysiological comparisons between different stimulus locations problematic. Retinotopy-constrained source estimation (RCSE) uses distributed dipole models simultaneously constrained by multiple stimulus locations to provide separation between individual visual areas that is not possible with conventional source estimation methods. Magnetoencephalography and RCSE were used to estimate time courses of activity in V1, V2, V3, and V3A. Responses to left and right hemifield stimuli were not significantly different. Peak latencies for peripheral stimuli were significantly shorter than those for perifoveal stimuli in V1, V2, and V3A, likely related to the greater proportion of magnocellular input to V1 in the periphery. Consistent with previous results, sensor magnitudes for lower field stimuli were about twice as large as for upper field, which is only partially explained by the proximity to sensors for lower field cortical sources in V1, V2, and V3. V3A exhibited both latency and amplitude differences for upper and lower field responses. There were no differences for V3, consistent with previous suggestions that dorsal and ventral V3 are two halves of a single visual area, rather than distinct areas V3 and VP.